TEACHER PERCEPTION ON THE USE OF WHATSAPP IN TEACHING ENGLISH DURING THE COVID-19 PANDEMIC - Agustina Risu, Indah; Marhum, Mochtar; Budi, Budi; Dewi, Anjar Kusuma (e-Journal of ELTS (English Language Teaching Society), 2023)
This research aimed to discover teachers' perceptions of the use of WhatsApp in teaching English. The researcher used descriptive qualitative research. The subject of this research was the English teachers at SMP Negeri 3 Poso Pesisir. An interview was used to collect the data. In the qualitative method, the data was analyzed using data reduction, display, and conclusion drawing. The result shows that the teachers perceived the use of WhatsApp are able to facilitate the learning process during COVID-19 Pandemic, especially for teaching English. Teachers used it as a facilitation tool for managing students’ tasks, posting material related to teaching English, organizing WhatsApp, and accommodating students’ interaction. In addition, teachers can manage large classes efficiently because technology takes it as an alternative method for teaching during the pandemic. The teacher can access the students' responses anytime in any place, and also, teachers can give feedback directly. WhatsApp provides the chance to learn not only at school but also at home or in any place. However, some factors limit the use of WhatsApp, such as highly consumed data plan, lack of familiarity with the students in adoption of WhatsApp, and submitting assignments behind schedule. Teachers stated that using WhatsApp was very helpful for conducting their virtual classroom.